A comparative study on adult mortality of Nepal - Aryal, UR; Lohani, SP; Upadhaya, S; Sinha, RC (Kathmandu University Medical Journal, 2010)
Background: Adult mortality (15-49 years) is one of the major public health issues which remains neglected in many developing counties like Nepal. Only limited data are available which is insufficient to identify the cause and level of mortality among adults. Objectives: The aim of the study is to explore and compare the adult mortality rate of Nepal between 1996, 2001 and 2006 surveys. Materials and methods: This is comparative study conducted by using secondary data extracted from Nepal Family Health Survey (NFHS, 1996), National Census Report 2001 and Nepal Demographic and Health Survey (NDHS, 2006). Statistical analysis was done using Microsoft excel soft ware. The adjusted mortality rates were computed using 2001 census population as standard population. Result: This studied showed there was statistical evidence of declining age specific mortality rate between 1996 and 2006 survey for both men and women respectively (p<0.05). Annually adult men mortality rate and adult women mortality rate was found to be declining by 1% and 3.2% respectively. Women mortality rate declined by 2.26 times as compared to men mortality rate over ten year's period. Conclusion: There is a need of in-depth analysis of adult mortality in the developing countries like Nepal. Key words: Adult mortality; Nepal DOI: 10.3126/kumj.v7i3.2732 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 246-251